Ian Frank Keymer. (8th September 2018) - Wells, Gerald; Malley, Dermod; Simpson, Vic
Abstract : A country boy who became, and remained, a countryman at heart. He was fascinated by diseases of wildlife and collaborated with others to publish widely on the topic.